Răspuns:
Explicație pas cu pas:
nu este o ecuatie
[tex]\sqrt{2}*(\frac{4}{\sqrt{18}} + \sqrt{0,(2)} ) + \sqrt{3} * (\sqrt{0,(3)}+\frac{2}{\sqrt{3}})=\\[/tex]
[tex]=\sqrt{2}*(\frac{4}{3\sqrt{2}} + \sqrt{\frac{2}{9}} ) + \sqrt{3} * (\sqrt{\frac{3}{9} }+\frac{2}{\sqrt{3}})\\[/tex]
[tex]=\sqrt{2}*(\frac{4}{3\sqrt{2}}+\frac{\sqrt{2} }{3} ) + \sqrt{3} * (\frac{\sqrt{3} }{3} +\frac{2}{\sqrt{3}})\\[/tex]
[tex]= \frac{4\sqrt{2}}{3\sqrt{2}}+\frac{\sqrt{2}*\sqrt{2} }{3} + \frac{\sqrt{3}*\sqrt{3} }{3} +\frac{2\sqrt{3}}{\sqrt{3}}\\[/tex]
[tex]= \frac{4}{3} + \frac{2}{3} + \frac{3}{3} + 2\\[/tex]
[tex]=\frac{9}{3} + 2 = 3 + 2 = 5\\[/tex]